Introducing blended learning practices in our classrooms - Win, N. L.; Wynn, S. D. (2015)
Blended learning has been received great interest in higher education around the world since it can increase access and flexibility for learners, increase level of active learning and achieve better student experiences and outcomes. Blended learning becomes popular to Higher Education Institutions community in Malaysia since a number of public and private universities were committed to bring the blended learning approach in their teaching and learning activities. Medium-impact blended learning has been used in BEng in Civil Engineering Programme, Bachelor Degree in International Business Programme and UK Degree Transfer Law Programme at INTI International University, Malaysia. Teaching techniques used in our classrooms were raptivity, flipped classroom and assessment and rubric on blackboard. The objectives of this study are to provide information on a variety of learning and teaching strategies that used in engineering and law subjects to support blended learning and to find out the perception of students on blended learning practices introduced in their classrooms. As for an academic, more initial preparation time is required to design a suitable blended learning model. Based on the response from the students, about half of the respondents neither agreed nor disagreed with the statements for contentment with blended courses. About 25% of the respondents would like to have more blended courses. It may be concluded that most students were not comfortable with online activities and they still preferred the traditional classes although blended learning has the proven potential to enhance the effectiveness and efficiency of meaningful learning experiences.